2009
DOI: 10.1007/s11803-009-9074-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of micro vibration by viscous dampers

Abstract: This study proposes a micro vibration mitigation system using viscous dampers to solve the problem of vibration in a high-tech building. Due to the operating frequency of the air conditioners and fundamental mode of the fl oors, a resonant phenomenon is occasionally experienced at the upper levels of the structure. Several strategies were considered, and viscous dampers combined with a suspension system were chosen to mitigate this annoying situation. A theoretical analysis was fi rst executed to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…For example, Asfar and Akour [9] presented a numerical study for the suppression of self-excited oscillator using an impact viscous damper. Lin et al [10] proposed a micro vibration mitigation system using viscous dampers to reduce the vibration in a high-tech building. Hong et.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Asfar and Akour [9] presented a numerical study for the suppression of self-excited oscillator using an impact viscous damper. Lin et al [10] proposed a micro vibration mitigation system using viscous dampers to reduce the vibration in a high-tech building. Hong et.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Hwang et al 16 studied the seismic protective systems for high-tech structures, and found that the incorporation of viscous dampers not only enhance the seismic safety but also minimize the micro-vibration of the structure. Lin et al 17 proposed a micro vibration mitigation system using viscous dampers for high-tech buildings, and results presented that the vibration can be effectively captured by the viscous damper and converted to lower frequencycontent tremors. Shih et al 18 studied the effect of different damper for high-tech buildings, and found the Velocity and Displacement Hydraulic Damper has superior vibration-reduction capability in reducing vibration.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies used isolators or dampers to reduce vibration for high-tech buildings. 1623 Hwang et al. 16 studied the seismic protective systems for high-tech structures, and found that the incorporation of viscous dampers not only enhance the seismic safety but also minimize the micro-vibration of the structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other one is to correct the DFT spectrum directly in frequency domain. Existing spectrum correction methods [7][8][9] use the main spectral line and some near the main one of DFT to get higher accuracy parameters of the signal. However, the accuracy of these correct methods is limited for the used spectral lines containing the truncation aliasing error.…”
Section: Introductionmentioning
confidence: 99%